Validação clínica do diagnóstico de enfermagem síndrome do idoso frágil - Oliveira, Fabiana Maria Rodrigues Lopes de (2019)
Frailty has no consensus on its theoretical definition in the gerontological literature, and in view of the multifactorial and multidimensional characteristic of the syndrome, it becomes complex to delimit operational attributes that are reliable to the aspects experienced by the frail elderly people. Thus, the elements of the nursing diagnosis Frail Elderly Syndrome contained in NANDA-I may not be accurate to reveal the reality experienced by frail elderly. Objective: To clinically validate the nursing diagnosis of NANDA-I Frail Elderly Syndrome in hospitalized elderly people. Method: This is a methodological study conducted with 40 elderly patients admitted to the two clinical units of the Lauro Wanderley University Hospital, João Pessoa, Paraíba, Brazil. To accomplish this, the last phase of the Hoskins Nursing Diagnosis Validation Model was adopted: clinical validation. Data collection was performed from August to December 2018, in the referred hospital, by performing the first stage of the Nursing Process. This stage was carried out simultaneously by two nurses, doctoral students in nursing and with experience in the health area of the elderly person. Data analysis was performed using a quantitative approach using descriptive statistics of univariate nature for all variables. In addition, agreement tests were used on the presence or absence of diagnostic indicators (Kappa), in addition to the weighted reliability coefficient between the diagnoses and the calculation of the total diagnosis score. The study was approved by the research ethics committee of the referred hospital with protocol number: 3,328,306. In order to better understand the phenomenon, a chapter on the state of the art of frailty was also developed, operationalized through an integrative literature review. Results: the nursing diagnosis NANDA-I Taxonomic Frail Elderly Syndrome has 13 defining characteristics, 19 risk factors, 10 identifiers of populations at risk and 14 associated conditions. Nine defining characteristics were validated in our context: impaired gait; decreased cardiac output; self-care deficit for bathing; self-care deficit for intimate hygiene; self-care deficit to dress; fatigue; activity intolerance; impaired physical mobility and unbalanced nutrition: less than body needs); 7 risk factors (impaired balance; decreased muscle strength; muscle weakness; activity intolerance; mean daily physical activity lower than recommended for age and sex; fear of falls and impaired physical mobility); 6 at-risk populations (low educational level; economically disadvantaged; history of falls; prolonged hospitalization; age over 70 years and female); and 2 associated conditions (walking less than four meters requires more than five seconds and chronic disease). Moreover, the agreement for this diagnosis was 0.78 (kappa), the reliability coefficient was 0.96, and the total score was 0.69. Conclusion: the validation of the nursing diagnosis Frail Elderly Syndrome in our sociocultural context was adequate. In this sense, this study is expected to contribute to the theoretical basis that provides support for critical thinking and diagnostic reasoning of nurses who experience care for the frail elderly person.